Effectiveness of short-term cycling interventions in older adults: a randomized trial of hypoxic, blood flow restriction, and eccentric cycling - Tom Citherlet; Gustavo R. Mota; Marco Carletta; Kevin Hayoz; Daniel Silva Pereira; Grégoire P. Millet (Scientific Reports)
Abstract We evaluated whether a short-term cycling intervention in hypoxia, with blood flow restriction, or eccentric cycling induces greater health benefits than traditional cycling in older adults. Fifty-five individuals (68 ± 4 year, 25 females) performed supervised moderate-intensity intermittent training (MIIT) three times weekly for 4 weeks, assigned to one of four groups: HYP (hypoxic chamber, FiO₂ 14%), BFR (thigh cuffs at ≈ 350 mmHg, deflated between sets), ECC (eccentric ergocycle), or CON (traditional ergocycle). Pre- and post-training assessments covered cardiovascular function, quality of life, cognition, aerobic fitness, skeletal muscle oxidative capacity, knee extensors and flexors strength, and thigh volume. Training interventions improved the 6-min cycling test average power output (9 ± 15%, P < 0.001), isokinetic at different speeds (10 ± 16 to 20 ± 26%, all P < 0.001) and isometric peak torques (14 ± 15%, P < 0.001), thigh circumference (1 ± 2%, P = 0.008), diastolic pressure (−3 ± 8%, P = 0.021), resting heart rate (−3 ± 7%, P = 0.004), digit span (9 ± 21%, P = 0.031) and TMT-B performance (−1 ± 51%, P = 0.045) in all groups. However, no significant differences were observed between groups. These results confirm the efficacy of MIIT in older adults and suggest that exercise per se is more important than the specific modalities. Short-term (4-week) MIIT programs promote healthy aging, regardless of the training modality, which may encourage older adults to take action.